Microsurgery Recontruction in Plastic Surgery Division FKUI-RSCM, From 2009 - 2010 - Atmodiwirjo, Parintosa; Adhistana, Prasasta (Jurnal Plastik Rekonstruksi, 2012)
Microvascular surgery is the ability to repair very small blood vessels. Once the technique is mastered it becomes possible to revascularize and replant incomplete or complete digital amputations, and to design free tissue transfer procedures for the reconstruction of a large variety of damaged parts. This study included 17 cases of microsurgery in the last 1 years admitted to Division of Plastic and Reconstructive Surgery RSCM between February 2009 to February 2010. All patient were subjected to through clinical examination and appropriate laboratory and radiological investigations. Trauma is the most common etiology of soft tissue defect (10 cases, 58,8%), followed by tumor and infection (5 and 2 cases respectively). Defect is located 35,3% on the head/neck, 23,6% on the knee/lower leg, 23,6% on ankle/foot, and 17,6% on upper extremity. In this study we performed 9 anterolateral thigh (ALT), 6 radial forearm, 1 chimera flap, and 1 fibula flap. Flaps were vital in 13 cases, compromised in 4 cases, with 2 of them salvaged and survived. Vitality rate of ALT flap was 88,9% (7 vital, 1 non vital, 1 salvaged), 83,8% in RFFF (4 vital, 1 non vital, 1 salvaged) and 100% in fibular flap. The use of microvascular techniques has revolutionized reconstruction method and expanded the range of options for reconstructing a large anatomic defects in patients. If compare with advance center, the success of micro-surgery in our division is still under them. Expected to be approached with increasing operator experience and number of cases was undertaken.